Framing an execution ABC News & the case of Mumia Abu Jamal - Jhally, Sut; Gardner, Tom; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 2001)
In the 1990's, Mumia Abu-Jamal, an African American journalist on death row, became a symbol of the inequities in the United States judicial system. This film examines how ABC reporter Sam Donaldson's framing of Abu-Jamal's case stands up to the available facts and how it measures up to basic journalistic standards of fairness, balance, and accuracy
Title from title screen
Camera, Robbie Leppzer, Kelly Garner ; editors, Sut Jhally, Kelly Garner ; music, Thom Monahan
Narrator: Danny Glover
Features: Mike Farrell, Angela Davis, Janine Jackson, Tom Gardner, Leonard Weinglass, John Bracey
Keywords: Abu-Jamal, Mumia; Journalistic ethics; Journalism -- Objectivity; Journalism -- Standards